2012
DOI: 10.1039/c2jm33245k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene exfoliation in organic solvents and switching solubility in aqueous media with the aid of amphiphilic block copolymers

Abstract: The successful exfoliation of graphite to graphene sheets in liquid phase via tip sonication was achieved. A number of solvents were examined for several time periods and it was found that o-dichlorobenzene (o-DCB) and N-methyl-1,2-pyrolidone (NMP) are ideal solvents to exfoliate graphite and produce stable dispersions of graphene. The exfoliated graphene dispersions were characterized by complementary techniques including AFM, DLS, TGA and Raman. Furthermore, treatment of stable dispersions of exfoliated grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 45 publications
5
66
0
Order By: Relevance
“…10 The concentration of graphene in solvent against the exfoliation time plot is shown in the inset Figure 1. The concentration of the synthesized graphene sheets also increased remarkably with the increasing sonication time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The concentration of graphene in solvent against the exfoliation time plot is shown in the inset Figure 1. The concentration of the synthesized graphene sheets also increased remarkably with the increasing sonication time.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was only based on sonication and the sonication time was varied up to 5 hours. Skaltsas et al 10 have exfoliated graphene in o-DCB and N-methyl-1,2-pyrolidone via tip sonication for various exfoliation time up to 1 hour. Hamilton et al 16 have demonstrated the production of graphene dispersions from synthetic graphite, HOPG and expanded graphite in o-DCB by cup-horn sonication for 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown recently that the exfoliated graphene in NMP can be stabilized with an acidic solution of the poly(isopreneb-acrylic acid) (PI-b-PAA) or poly[styrene-b-(2-vinylpyridine)] (PS-b-P2VP) block copolymers [197] (Figure 10). Unfortunately, the thickness of graphitic flakes amounts to 44 nm and 2.5 nm respectively, implying that the PI-b-PAA-and/or PS-b-P2VP-assisted UILPE protocol needs to be further optimized.…”
Section: Reviewmentioning
confidence: 99%
“…Over the past years, it has been proven that graphene can be dispersed in water by using a wide range of polymers acting as DSAs, [14,195,197,198,[215][216][217][223][224][225][226][227][228][229][230][231][232] such as cellulose acetate (CA), [233] ethyl cellulose (EC), [229] polyvinylpyrrolidone (PVP), [224] lignin, [230] gum arabic (GA), [225,226] gelatin derived from animal skin and bones, [227] and even more complex systems such as bovine serum albumin (BSA), [223] hyaluronan (PyHA) [216] and DNA [198] functionalized with pyrene head-groups.…”
Section: Polymers As Dsasmentioning
confidence: 99%